Evaluation of recycled gravel in the concrete mixture for the surface layer of rigid flooring - Akihito Boa Esperança; Jésena Bernardo; Lino Maia (Global Journal of Ecology - Peertechz Publications, 2023)
Paving with recycled aggregates has already been widely carried out in some countries where there is already consolidated knowledge on the subject. This work analyzes in the laboratory the physical and mechanical behavior aspects of recycled aggregate in concrete mixes for rigid pavements. After selective collection at a construction site, the waste undergoes a crushing process, subsequent to granulation and separation into fractions to be used again in the realization of a new mixture with 40 and 100% replacement of natural gravel for recycled with the addition of structural concrete fibers that decrease shrinkage and increase final strength. In the same mix, these mixtures were compared with a conventional mixture that obtained better performance and presented greater compressive strength. The study sought to analyze the technical feasibility of using recycled material, testing the thickness of several concrete slabs for application on the pavement. Thus, it is concluded that the analyzed recycled aggregate is of promising use in hard pavement coating, as it presents a compressive strength superior to 25 MPa.